Enzymatic hydrolysis of cellulose (II): x-ray photoelectronic spectroscopy studies on cellulase adsorption. Effect of the surfactant tween 85 - Gama, F. M. (1997)
The adsorption of proteins on particulate and fibrous celluloses was studied by means of X-ray photoelectron spectroscopy (XPS). The presence of protein (bovine serum albumin and Celluclast, a commercial cellulase from Trichoderma reesei) adsorbed on the fibres was detected by N1 s signal in the wide-field spectrum. The proteins adsorbed onto several types of cellulose could be compared, irrespective of the fibres' specific surface area. The fractional monolayer coverage of cellulose fibres could also be calculated. The influence of surfactant Tween 85 on cellulase adsorption and enzymatic activity was also investigated. At low enzyme concentrations, the surfactant reduces the amount of adsorbed enzyme, simoultaneously improving the reaction rate. The effect of the surfactant depends on the structural properties of the substrate. The higher the crystallinity of the substrate, the less effective is the enhancement of the reaction and the reduction of the amount of the adsorbed enzyme by the surfactant.